Assessment of the dinitrogen released as ammonium and dissolved organic nitrogen by unicellular and filamentous marine diazotrophic cyanobacteria grown in culture - Berthelot, Hugo; Bonnet, Sophie; Camps, Mercedes; Grosso, Olivier; Moutin, Thierry (Frontiers in Marine Science, 2015)
The dinitrogen (N2) released as dissolved nitrogen (DN) has been compared in batch cultures of four marine diazotrophic cyanobacteria: the colony forming Trichodesmium IMS101 and the unicellular strains Cyanothece ATCC51142, Crocosphaera watsonii WH8501 and WH0003. Two approaches were conducted for this purpose. The first approach consisted in the comparison of the total accumulation of fixed N2 in the culture (both in dissolved and particulate pools) with the net N2 fixation rates (i. e. the fixed N2 incorporated only in the particulate fraction after 15N2 incubation). The difference between the two measures accounted for the fixed N2 released as DN. The second approach consisted in the direct measure of the 15N-enrichment of ammonium (NH4+) and dissolved organic N (DON) following the 15N2 incubations. The N2 released as DN accounted for 0 - 20 % and 1 % of the N2 fixed after 24 h in the first and second approach, respectively. We show that the recent methodological improvements in the net N2 fixation determination applied in this study tend to reconcile the two approaches that formerly led to contrasted values. However, the large analytical uncertainties of the first approach limit its reliability. Thus, the direct determination of the 15N-enrichment of the dissolved pool remains the best tool to assess the fixed N2 released in the DN pool, in particular as it allows shorter incubation times. There were no clear patterns detected between the filamentous Trichodesmium and unicellular strains, neither in terms of the amount of N2 released as DN nor in terms of the proportion of NH4+ relative to DON. This suggests that N2 release processes are shared among the filamentous and free living diazotrophs.